Analisis Perbandingan Kinerja Karyawan Tetap Dan Karyawan Kontrak Pada PT. Bank Mandiri (Persero)Tbk Cabang Kedungdoro Surabaya - Ella Aprillia (PRAGMATIS, 2021)
The purposed of this study was to determine the differences in the performance of permanent employees and contract employees. In this research, the company that was used to research was PT. Bank Mandiri Persero Tbk and using quantitative research and data obtained directly from respondents as well as literature, documents and reports related to research and sample problems used in this study is simple saturated with the number of samples of 21 permanent employees and 21 contract employees (outsourching) and a total of 41 samples using saturated sample methods and analysis techniques used in this study are data analysis techniques used are normality tests and independent sample t-test using the program SPSS Version 16.0. Based on the results of the normality test in the data Kolmogorov-Smirnov got a result of 0.281 greater than 0.05 And in accordance with the test criteria can be done that in the table is distributed normally. Independent Sample T-Test results in the equal Variances Assumed section are known sig values. (2-tailed) by 0.006 < 0.05. These results show that Ho was rejected and Ha accepted.